Systems and procedures of certification of qualifications in Ireland - Conway, Miriam [Verfasser]; Lambkin, Angela [Verfasser] (My University, 1994)
The aim of this report is to profile systems, structures and procedures for the assessment of competencies and awarding of qualifications in the vocational education and vocational training sectors in Ireland. Chapter 1 profiles the awarding bodies and their responsibilities for certification in vocational education and training. Chapter 2 describes access and progression to certification and outlines new programmes and schemes developed to expand routes to certified qualifications. Chapter 3 indicates the techniques for the assessment and certification of competencies. Chapter 4 highlights new developments in the area and trends in the certification process. (BIBB-Doku)
Keywords: L 7 Prüfungen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2.1 Westeuropa; Bildungsabschluss; Qualifikationsnachweis; Anerkennung; Zertifizierung; Irland